Value of adding 0.01% atropine with orthokeratology for myopia in children: an updated meta-analysis of randomized controlled trials - Shudan Tu; Huangfang Ying; Liyang Ni; Zilong Zhang; Weiping Hu (Frontiers in Pediatrics)
BackgroundThis systematic review and meta-analysis aimed to compare outcomes of 0.01% atropine with orthokeratology (AOK) vs. orthokeratology (OK) alone for slowing the progression of myopia in children.MethodsMEDLINE via PubMed, Embase, Scopus, Web of Science, CENTRAL (Cochrane Central Register of Controlled Trials), Chinese electronic databases of VIP, and Wanfang were searched from inception until 19th August 2024 for randomized controlled trials (RCTs) about the review topic. The primary outcome was a change in axial length (AL) (mm). Secondary outcomes were spherical equivalent refraction (SER) (Diopter), pupil diameter (PD) (mm), amplitude of accommodation (AA) (Diopter), and intraocular pressure (IOP) (mmHg).Results10 articles corresponding to eight RCTs were included. Meta-analysis found that change in AL was significantly reduced with AOK as compared to OK alone at 6 months (MD: −0.10 95% CI: −0.14, −0.06 I2 = 48%), 12 months (MD: −0.08 95% CI: −0.10, −0.07 I2 = 0%) and 24 months (MD: −0.14 95% CI: −0.19, −0.08 I2 = 0%). Pooled analysis found that AOK did not reduce the progression of SER (MD: 0.06 95% CI: −0.00, 0.12 I2 = 7%) and increased PD (MD: 0.63 95% CI: 0.40, 0.85 I2 = 86%) as compared to OK alone. Pooled analysis also found a tendency of reduced AA with AOK as compared to OK alone but without significant results (MD: −0.45 95% CI: −1.00, 0.10 I2 = 59%). Meta-analysis failed to show a statistically significant difference in change of IOP between AOK and OK (MD: −0.49 95% CI: −1.48, 0.50 I2 = 51%).ConclusionsAOK seems to be more efficacious in slowing the progression of myopia in children as compared to OK alone.